Effect of different hand positions on elbow loading during the round off in male gymnastics: a case study - Farana, R.; Janezckova, P.; Uchytil, J.; Irwin, G. (Science of Gymnastics Journal, 2015)
Elbow lesions are a potential reason for ending a gymnastics career, and presents a real concern for coaches, scientist and clinicians. Previous research has focused on female gymnastics and as such the aim of the current study was to investigate key elbow joint injury risk factors including impact forces, elbow joint kinetics, and kinematics during different roundoff techniques in male artistic gymnastics. An international level active male gymnast performed 15 successful trials of a round-off from a hurdle step to back handspring with three different hand positions (parallel (5), T-shape (5) and reverse (5)). Synchronized kinematic (3D-automated motion analysis system; 240 Hz) and kinetic (force plate; 1200 Hz) data were collected for each trial. Effect-size statistics determined differences between each hand position. The key conclusions were, the T-shape technique reduces vertical, anterior-posterior and resultant ground reaction forces. Differences in elbow joint internal adduction moment and elbow joint compression force indicated that the T-shape technique may prevent elbow joint complex overload and reduces potential of elbow injuries.